Bamboo-based porous carbon microspheres as well as preparation method and application thereof
By using bamboo-based porous carbon microspheres as electrode materials, the problems of insufficient conductivity and hydrophilicity of existing electrode materials are solved, and efficient capacitive deionization performance and feasibility of industrial preparation are achieved.
Patent Information
- Application Number
- CN202411797610.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-03-04
AI Technical Summary
The existing electrode materials have poor conductivity, insufficient hydrophilicity, complex and high cost in capacitive deionization technology, which limits their promotion in industrial applications.
Bamboo-based porous carbon microspheres are used as electrode materials, and curing and pyrolysis are prepared by spray pyrolysis method to obtain materials with porous structure, rich adsorption sites, and good conductivity and hydrophilicity.
It has achieved efficient water desalination and purification performance, significantly improved the electrical conductivity and hydrophilicity of the material, simple preparation process, low cost, meets industrial production requirements, and shows good cycle stability in regeneration cycle experiments.
Smart Images

Figure CN119551656A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of capacitive deionization, and in particular to bamboo-based porous carbon microspheres and a preparation method and application thereof. Background Art
[0002] Capacitive deionization technology has received extensive attention in recent years due to its advantages such as environmental protection, low energy consumption and low cost, and has been widely used in water desalination and purification. The theoretical basis of this technology is the double-layer capacitance effect: when a voltage is applied between two electrodes, the electrode plates carry positive and negative charges respectively, and the positive and negative ions in the solution are adsorbed on the surface or pores of the electrode material under the action of electrostatics, forming a double-layer structure, thereby achieving desalination and purification of the aqueous solution.
[0003] In capacitive deionization technology, electrode materials are the core. Ideal electrode materials need to have the following characteristics: high effective specific surface area to provide sufficient ion adsorption sites, reasonable pore size distribution to optimize mass transfer performance, excellent conductivity to reduce resistance loss, good hydrophilicity to enhance ion diffusion capacity, and excellent chemical stability to adapt to a variety of complex working conditions. However, existing electrode materials have certain shortcomings in these aspects. For example, although the commonly used carbon-based electrode materials have a high specific surface area, they usually have poor conductivity and insufficient wettability. At the same time, the preparation process is complicated and the cost is high. These problems seriously restrict their promotion in industrial applications.
[0004] Chinese patent document CN112010404A discloses a capacitor deionization electrode material based on organic small molecule cracked carbon. The material is prepared by solid phase synthesis, and the process is relatively simplified, which is conducive to industrial production. However, similar to traditional carbon-based electrode materials, the cracked carbon material still has the problem of weak hydrophilicity, resulting in the prepared capacitor deionization electrode having less than ideal performance in desalination tests. This defect of insufficient hydrophilicity limits the effect and scope of application of the material in practical applications.
[0005] Therefore, the development of a new electrode material that can overcome the shortcomings of existing technologies, especially a material with significant advantages in improving hydrophilicity, conductivity and feasibility of industrial preparation, is the key to the further development of capacitive deionization technology. At the same time, the material must have high desalination performance, environmental friendliness and economy to meet the diverse needs of future water treatment technologies. Summary of the invention
[0006] One of the purposes of the present invention is to provide a method for preparing bamboo-based porous carbon microspheres. The bamboo-based porous carbon microspheres prepared by the method have good hydrophilicity and are rich in adsorption sites and ion transmission channels.
[0007] In order to achieve the above object, the present invention adopts the following technical scheme: a method for preparing bamboo-based porous carbon microspheres, comprising the following steps: S1. Put the bamboo block into a sealed container, add organic base A and solvent B, react at 130-170°C (e.g., react for 1-5 h) to obtain a mixture, pulp the mixture, separate and obtain crude fiber, then put the crude fiber into solvent C, bleach at 50-70°C (e.g., bleach for 3-8 h), and then separate and obtain bamboo cellulose; S2. adding bamboo cellulose to solvent D, stirring at 50-80° C. (e.g., stirring for 4-6 h) until the bamboo cellulose is fully dissolved to obtain a bamboo cellulose solution; S3. The bamboo cellulose solution is diluted with an organic solvent, inorganic particles are added, and a dispersion is obtained after ultrasonic dispersion; S4. The dispersion is atomized and passed into a heating container, cured and pyrolyzed at 400-1200° C., and a mixed solution is obtained after cooling. The mixed solution is then ultrasonically dispersed and centrifuged to obtain a solid product, namely, bamboo-based porous carbon microspheres.
[0008] Furthermore, in step S1, the molar ratio of the organic base A to the solvent B is 1:(4-16).
[0009] Furthermore, in step S1, the organic base A is selected from at least one (for example, one of) dibutylamine, tetramethylguanidine, N-methylformamide, and pyrrolidone.
[0010] Furthermore, in step S1, the solvent B is selected from at least one (eg, one or two) of tetrahydrofuran, N,N-dimethylformamide and water.
[0011] Furthermore, in step S1, the solvent C is an aqueous solution containing 0.3-1% by mass of hydrogen peroxide, 0.2-0.5% by mass of sodium hydroxide, 0.02-0.05% by mass of magnesium sulfate, and 0.05-0.3% by mass of sodium silicate.
[0012] Furthermore, in step S1, every 1g of bamboo block corresponds to 10mL of solvent C. For example, when the amount of bamboo block is 3g, the amount of solvent C is 30mL; when the amount of bamboo block is 5g, the amount of solvent C is 50mL.
[0013] Furthermore, in step S2, the solvent D is a LiCl / DMAc solution with a concentration of 6%-10%.
[0014] Furthermore, in step S2, the mass ratio of the bamboo cellulose to the solvent D is 1:(60-80).
[0015] Furthermore, in step S3, the organic solvent is ethylene glycol or N,N-dimethylformamide.
[0016] Furthermore, in step S3, the solid content of the diluted bamboo cellulose solution is 1% to 1.5%.
[0017] Furthermore, in step S3, the inorganic particles are selected from at least one (for example, one) of nano calcium carbonate, lithium chloride, potassium chloride, and sodium chloride.
[0018] Furthermore, in step S3, the mass ratio of bamboo cellulose to inorganic particles in the dispersion is 1:(0.5-2).
[0019] Furthermore, in step S3, the specific steps of atomizing the dispersion and then passing it into the heating container include: atomizing the dispersion (for example, adding the dispersion to an ultrasonic atomization device), and feeding the atomized dispersion in the form of droplets through a pipe (such as a quartz conduit) into the heating container for curing and pyrolysis.
[0020] Wherein, the heating container involved in the above preparation method can be a high-temperature tube furnace.
[0021] Another object of the present invention is to provide a bamboo-based porous carbon microsphere, which is prepared by the above-mentioned preparation method. The bamboo-based porous carbon microsphere has a porous microsphere morphology.
[0022] In addition, the present invention also provides a capacitor deionization electrode material, which includes the above-mentioned bamboo-based porous carbon microspheres.
[0023] In addition, the present invention also provides an application of a capacitor deionization electrode material. Specifically, the capacitor deionization electrode material can be used to remove tetracycline antibiotics in water.
[0024] The preparation method adopted by the present invention involves less reaction reagents in the preparation process, and the product is pollution-free, which meets the requirements of green chemistry. In addition, the present invention adopts spray pyrolysis and carbonization to prepare bamboo-based porous carbon microspheres with porous microsphere morphology. The process can be expanded on a large scale, which meets the requirements of efficient and low-cost preparation. It is particularly worth mentioning that the bamboo-based porous carbon microspheres synthesized by the present invention have the characteristics of being porous, large specific surface area, and dual-doped with nitrogen / oxygen elements. The material has good electrical conductivity and hydrophilicity, and has abundant adsorption sites and ion transmission channels. After testing, the material has a high adsorption capacity and shows good cycle stability in the regeneration cycle experiment. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 is a SEM image of the bamboo-based porous carbon microspheres prepared in Example 1; Figure 2TEM image of the bamboo-based porous carbon microspheres prepared in Example 1; Figure 3 This is the infrared detection image of the bamboo-based porous carbon microspheres prepared in Example 1 before and after TC adsorption. DETAILED DESCRIPTION
[0026] In order to facilitate the understanding of those skilled in the art, the present invention is further described below in conjunction with the examples, and the contents mentioned in the examples are not limitations of the present invention. It should be noted in advance that the following examples were completed in the laboratory, and those skilled in the art should understand that the amounts of the components given in the examples only represent the ratio relationship between the components, rather than specific limitations.
[0027] The present invention mainly uses bamboo cellulose solution as a matrix and inorganic particles as porogens, and prepares bamboo cellulose-based porous carbon by one-step solidification and pyrolysis of bamboo cellulose / inorganic particle dispersion by spray pyrolysis. The specific steps are as follows: 1. Put the washed and dried bamboo blocks into a sealed container, add organic base A and solvent B, react at 130-170°C for 1-5 hours to obtain a mixture, then pulp the mixture, separate and wash to obtain crude fiber, then add the crude fiber into solvent system C for bleaching, keep the temperature at 50-70°C, treat for 3-8 hours, and then separate to obtain bamboo cellulose; 2. Add the extracted bamboo cellulose to a certain amount of solvent system D, and stir at 50-80°C for 4-6 hours until the bamboo cellulose is fully dissolved to obtain a bamboo cellulose solution; 3. diluting the bamboo cellulose solution with an organic solvent, adding an appropriate amount of inorganic particles, and then dispersing by ultrasonication to obtain a dispersion system; Fourth, the dispersion system is atomized and introduced into a high-temperature tube furnace filled with nitrogen, and one-step solidification and pyrolysis is performed at 400-1200°C. After natural cooling, the pyrolysis product is washed and collected with ethanol to obtain a mixed solution. Deionized water and dilute hydrochloric acid are added to the mixed solution, and ultrasonic dispersion and washing and centrifugation are performed. The supernatant is poured off, and the solid product is collected and dried for 1-2 days to obtain bamboo charcoal microspheres with a porous structure.
[0028] In step 1, the molar ratio of the organic base A to the solvent B is about 1:(4-16).
[0029] In step 1, the organic base A is selected from at least one of dibutylamine, tetramethylguanidine, N-methylformamide and pyrrolidone.
[0030] In step 1, solvent B is selected from at least one of tetrahydrofuran, N,N-dimethylformamide and water.
[0031] In step 1, the solvent system C is an aqueous solution containing 0.3-1% by mass of hydrogen peroxide, 0.2-0.5% by mass of sodium hydroxide, 0.02-0.05% by mass of magnesium sulfate, and 0.05-0.3% by mass of sodium silicate.
[0032] In step 2, the solvent system D is a LiCl / DMAc solution with a concentration of 6%-10%.
[0033] In step 2, the mass ratio of solute (bamboo cellulose) to solvent (solvent system D) is 1:(60-80).
[0034] In step 3, the organic solvent is ethylene glycol or N,N-dimethylformamide.
[0035] In step 3, the solid content of the bamboo cellulose solution after dilution is 1% to 1.5%.
[0036] In step three, the inorganic particles are selected from at least one of nano calcium carbonate, lithium chloride, potassium chloride and sodium chloride.
[0037] In step three, the mass ratio of bamboo cellulose to inorganic particles in the dispersion system is 1:(0.5-2).
[0038] In step three, the dispersion system is added to an ultrasonic atomization device, and the atomized dispersion is sent to a high-temperature furnace in the form of droplets through a quartz conduit for curing and pyrolysis.
[0039] The above preparation process is simple, low-cost and high-efficiency. The prepared bamboo cellulose-based carbon material has a particle size of 0.5-2 μm, has a high nitrogen / oxygen doping and interconnected porous structure, and exhibits excellent capacitive deionization performance.
[0040] The following is further explained with specific examples. Example 1
[0041] 1. Extraction of bamboo cellulose 5 g of washed and dried bamboo blocks were placed in a sealed container, and 25 mL of N-methylformamide and 25 mL of water were added respectively. The mixture was reacted at a high temperature of 130 ° C for 1 h to obtain a mixture. The reaction mixture was stirred, filtered and washed. The filtered solid was placed in an aqueous solution containing 50 mL of 0.3% hydrogen peroxide, 0.2% sodium hydroxide, 0.02% magnesium sulfate and 0.05% sodium silicate, and bleached at 50 ° C for 3 h. Then bamboo cellulose was separated with a yield of 45.4% and an extracted solid cellulose content of 93.6%.
[0042] 2. Preparation of electrode adsorption materials (i) Add 2.27 g of the extracted bamboo cellulose into 181.6 g of a 6% LiCl / DMAc solution and stir at 50°C for 4 h until the bamboo cellulose is fully dissolved to obtain a bamboo cellulose solution.
[0043] (ii) Take 80 g of bamboo cellulose solution, add 18.4 g of N,N-dimethylformamide and dilute to a solid content of 1%, then add pre-dried nano-calcium carbonate (1.476 g). At this time, the mass ratio of bamboo cellulose to nano-calcium carbonate is about 1:1.5. After preliminary stirring, ultrasonic dispersion is performed to obtain a dispersion system.
[0044] (III) The dispersion system is atomized and introduced into a high-temperature tube furnace filled with nitrogen, and one-step solidification and pyrolysis are performed at 600°C. After natural cooling, the pyrolysis products are collected by washing with ethanol to obtain a mixed solution. Deionized water and dilute hydrochloric acid are added to the mixed solution, and ultrasonic dispersion and washing and centrifugation are performed. The supernatant is poured off, and the solid product is collected and dried for 1 day to obtain bamboo charcoal microspheres with a porous structure.
[0045] 3. Product morphology analysis and performance testing Figure 1 The morphology of the product under a scanning electron microscope is shown. Overall, the particle size of the product is about 0.5-1 μm, and it is in the form of porous microspheres. Figure 2 The microstructure of the product under transmission electron microscope is shown. Figure 2 It can be seen that the product has a loose tissue structure with a large number of microchannels formed in the tissue.
[0046] The bamboo-based porous carbon electrode sheet is composed of 80% active material (about 0.12 g of bamboo-based porous carbon), 10% conductive agent (about 0.015 g of Super P) and 10% binder (about 0.015 g of PTFE). First, the three materials are uniformly mixed into a slurry in an ethanol solution, and then rolled into a sheet with a thickness of 0.1 mm, an area of 4.0 cm × 4.0 cm and a weight of 40 mg, which is then pressed on graphite paper and placed in a 120°C oven for drying for 24 h to obtain a bamboo-based porous carbon electrode sheet for CDI devices.
[0047] When conducting the experiment of tetracycline (TC) adsorption on bamboo-based porous carbon, the tetracycline adsorption performance test will be carried out on the CDI device. The experimental device consists of a 10 cm × 10 cm glass plate, a 2 cm thick silica gel sheet, a bamboo-based porous carbon electrode sheet and a graphite plate. A 1.2 V CDI is driven by a DC power supply and a peristaltic pump is used at a speed of 20 mL min. -1The treated solution was injected into the CDI device at a constant flow rate of 1.5 %. All experiments were carried out in a total volume of 100 mL of solution, the temperature was controlled at 298 K, and the absorbance of the solution after the test was measured at a wavelength of 358 nm.
[0048] Figure 3 The figure shows the functional group changes of the product before and after adsorption. After analysis, the sample after TC adsorption has a peak at 1110 cm -1 、1597 cm -1 and 2350 cm -1 There are obvious characteristic peaks on the left and right, which correspond to −OH, C=O and C−H groups respectively. Due to the electrostatic interaction and hydrogen bonding between these oxygen-containing functional groups and O and N with lone pairs of electrons in the TC molecule, TC is adsorbed on the sample surface. This shows that the bamboo cellulose-based porous carbon has a significant adsorption of tetracycline, and also shows good cycle stability in the regeneration cycle experiment (such as Figure 3 as shown). Example 2
[0049] 1. Extraction of bamboo cellulose 5 g of washed and dried bamboo blocks were placed in a sealed container, and 25 mL of N-methylformamide and 25 mL of water were added respectively. The mixture was reacted at a high temperature of 140°C for 2 h to obtain a mixture. The reaction mixture was stirred, filtered and washed. The filtered solid was placed in a 50 mL aqueous solution containing 1% hydrogen peroxide, 0.5% sodium hydroxide, 0.05% magnesium sulfate and 0.3% sodium silicate, bleached at 70°C for 8 h, and then separated to obtain bamboo cellulose with a yield of 47% and an extracted solid cellulose content of 96.9%.
[0050] 2. Preparation of electrode adsorption materials (i) Add 2.27 g of the extracted bamboo cellulose into 136.2 g of a 6% LiCl / DMAc solution and stir at 80°C for 6 h until the bamboo cellulose is fully dissolved to obtain a bamboo cellulose solution.
[0051] (ii) Take 80 g of bamboo cellulose solution, add 39.27 g of N,N-dimethylformamide and dilute to a solid content of 1.1%, then add pre-dried lithium chloride (1.312 g). At this time, the mass ratio of bamboo cellulose to lithium chloride is about 1:1. After preliminary stirring, ultrasonic dispersion is performed to obtain a dispersion system.
[0052] (III) The dispersion system is atomized and introduced into a high-temperature tube furnace filled with nitrogen, and one-step solidification and pyrolysis are performed at 400°C. After natural cooling, the pyrolysis products are collected by washing with ethanol to obtain a mixed solution. Deionized water and dilute hydrochloric acid are added to the mixed solution, and ultrasonic dispersion and washing and centrifugation are performed. The supernatant is poured off, and the solid product is collected and dried for 2 days to obtain bamboo charcoal microspheres with a porous structure.
[0053] 3. Product morphology analysis and performance testing The morphology of the product obtained in this example is similar to that in Example 1. The particle size of the product is about 0.5-1.5 μm, and it is in the form of porous microspheres. The product also has a loose organizational structure, a large number of microchannels are formed in the microspheres, and the surface is rich in nitrogen and oxygen elements.
[0054] The bamboo-based porous carbon electrode sheet is composed of 80% active material (about 0.15 g of bamboo-based porous carbon), 10% conductive agent (about 0.019 g of Super P) and 10% binder (about 0.019 g of PTFE). First, the three materials are uniformly mixed into a slurry in an ethanol solution, and then rolled into a sheet with a thickness of 0.1 mm, an area of 4.0 cm × 4.0 cm and a weight of 40 mg, which is then pressed on graphite paper and placed in a 120°C oven for drying for 24 h to obtain a bamboo-based porous carbon electrode sheet for CDI devices.
[0055] When conducting the tetracycline adsorption experiment on bamboo-based porous carbon, the tetracycline adsorption performance test will be carried out on the CDI device. The experimental device consists of a 10 cm × 10 cm glass plate, a 2 cm thick silica gel sheet, a bamboo-based porous carbon electrode sheet and a graphite plate. A 1.2 V CDI is driven by a DC power supply and a peristaltic pump is used at a speed of 20 mL min. -1 The treated solution was injected into the CDI device at a constant flow rate of 1.5 %. All experiments were carried out in a total volume of 100 mL of solution, the temperature was controlled at 298 K, and the absorbance of the solution after the test was measured at a wavelength of 358 nm.
[0056] The test found that the infrared spectra of the product obtained in this example before and after TC adsorption were similar to those in Example 1, both at 1110 cm -1 、1597 cm -1 and 2350 cm -1 There are obvious characteristic peaks on the left and right, indicating that the bamboo cellulose-based porous carbon has obvious adsorption of tetracycline, and also shows good cycle stability in the regeneration cycle experiment. Example 3
[0057] 1. Extraction of bamboo cellulose 5 g of washed and dried bamboo blocks were placed in a sealed container, and 35 mL of dibutylamine and 15 mL of water were added respectively. The mixture was reacted at a high temperature of 150 ° C for 3 h to obtain a mixture. The reaction mixture was stirred, filtered and washed. The filtered solid was placed in 50 mL of an aqueous solution containing 0.5% hydrogen peroxide, 0.5% sodium hydroxide, 0.03% magnesium sulfate and 0.1% sodium silicate, bleached at 60 ° C for 4 h, and then separated to obtain bamboo cellulose with a yield of 45.5% and an extracted solid cellulose content of 93.7%.
[0058] 2. Preparation of electrode adsorption materials (i) Add 2.28 g of the extracted bamboo cellulose into 159.6 g of 8% LiCl / DMAc solution and stir at 60°C for 5 h until the bamboo cellulose is fully dissolved to obtain a bamboo cellulose solution.
[0059] (ii) Take 80 g of bamboo cellulose solution, add 6.77 g of N,N-dimethylformamide and dilute to a solid content of 1.3%, then add pre-dried potassium chloride (2.256 g). At this time, the mass ratio of bamboo cellulose to potassium chloride is about 1:2. After preliminary stirring, ultrasonic dispersion is performed to obtain a dispersion system.
[0060] (III) The dispersion system is atomized and introduced into a high-temperature tube furnace filled with nitrogen, and one-step solidification and pyrolysis are performed at 400°C. After natural cooling, the pyrolysis products are washed and collected with ethanol to obtain a mixed solution. Deionized water and dilute hydrochloric acid are added to the mixed solution, and ultrasonic dispersion and washing and centrifugation are performed. The supernatant is poured off, and the solid product is collected and dried for 1.5 days to obtain bamboo charcoal microspheres with a porous structure.
[0061] 3. Product morphology analysis and performance testing The morphology of the product obtained in this example is similar to that in Example 1. The particle size of the product is about 0.5-2 μm, and it is in the form of porous microspheres. The product also has a loose organizational structure, a large number of microchannels are formed in the microspheres, and the surface is rich in nitrogen and oxygen elements.
[0062] The bamboo-based porous carbon electrode sheet is composed of 80% active material (about 0.12 g of bamboo-based porous carbon), 10% conductive agent (about 0.015 g of Super P) and 10% binder (about 0.015 g of PTFE). First, the three materials are uniformly mixed into a slurry in an ethanol solution, and then rolled into a sheet with a thickness of 0.1 mm, an area of 4.0 cm × 4.0 cm and a weight of 40 mg, which is then pressed on graphite paper and placed in a 120°C oven for drying for 24 h to obtain a bamboo-based porous carbon electrode sheet for CDI devices.
[0063] When conducting the tetracycline adsorption experiment on bamboo-based porous carbon, the tetracycline adsorption performance test will be carried out on the CDI device. The experimental device consists of a 10 cm × 10 cm glass plate, a 2 cm thick silica gel sheet, a bamboo-based porous carbon electrode sheet and a graphite plate. A 1.2 V CDI is driven by a DC power supply and a peristaltic pump is used at a speed of 20 mL min. -1 The treated solution was injected into the CDI device at a constant flow rate of 1.5 %. All experiments were carried out in a total volume of 100 mL of solution, the temperature was controlled at 298 K, and the absorbance of the solution after the test was measured at a wavelength of 358 nm.
[0064] The test found that the infrared spectra of the product obtained in this example before and after TC adsorption were similar to those in Example 1, both at 1110 cm -1 、1597 cm -1 and 2350 cm -1 There are obvious characteristic peaks on the left and right, indicating that the bamboo cellulose-based porous carbon has obvious adsorption of tetracycline, and also shows good cycle stability in the regeneration cycle experiment. Example 4
[0065] 1. Extraction of bamboo cellulose 3 g of washed and dried bamboo blocks were placed in a sealed container, and 10 g of pyrrolidone, 10 mL of tetrahydrofuran and 30 mL of water were added respectively. The mixture was reacted at a high temperature of 160 ° C for 4 hours to obtain a mixture. The reaction mixture was stirred, filtered and washed. The filtered solid was placed in an aqueous solution containing 30 mL of 0.5% hydrogen peroxide, 0.3% sodium hydroxide, 0.03% magnesium sulfate and 0.2% sodium silicate, bleached at 70 ° C for 7 hours, and then separated to obtain bamboo cellulose, with a yield of 46.1% and an extracted solid cellulose content of 95.1%.
[0066] 2. Preparation of electrode adsorption materials (i) 1.383 g of bamboo cellulose was extracted and added into 82.98 g of 10% LiCl / DMAc solution, and stirred at 70°C for 6 h until the bamboo cellulose was fully dissolved to obtain a bamboo cellulose solution.
[0067] (ii) Take 60 g of bamboo cellulose solution, add 5.6 g of ethylene glycol and dilute to a solid content of 1.5%, then add pre-dried nano-calcium carbonate (1.968 g). At this time, the mass ratio of bamboo cellulose to nano-calcium carbonate is about 1:2. After preliminary stirring, ultrasonic dispersion is performed to obtain a dispersion system.
[0068] (III) The dispersion system is atomized and introduced into a high-temperature tube furnace filled with nitrogen, and one-step solidification and pyrolysis are performed at 1200°C. After natural cooling, the pyrolysis products are collected by washing with ethanol to obtain a mixed solution. Deionized water and dilute hydrochloric acid are added to the mixed solution, and ultrasonic dispersion and washing and centrifugation are performed. The supernatant is poured off, and the solid product is collected and dried for 2 days to obtain bamboo charcoal microspheres with a porous structure.
[0069] 3. Product morphology analysis and performance testing The morphology of the product obtained in this example is similar to that in Example 1. The particle size of the product is about 1-2 μm, and it is in the form of porous microspheres. The product also has a loose organizational structure, a large number of microchannels are formed in the microspheres, and the surface is rich in nitrogen and oxygen elements.
[0070] The bamboo-based porous carbon electrode sheet is composed of 80% active material (about 0.15 g of bamboo-based porous carbon), 10% conductive agent (about 0.019 g of Super P) and 10% binder (about 0.019 g of PTFE). First, the three materials are uniformly mixed into a slurry in an ethanol solution, and then rolled into a sheet with a thickness of 0.1 mm, an area of 4.0 cm × 4.0 cm and a weight of 40 mg, which is then pressed on graphite paper and placed in a 120°C oven for drying for 24 h to obtain a bamboo-based porous carbon electrode sheet for CDI devices.
[0071] When conducting the tetracycline adsorption experiment on bamboo-based porous carbon, the tetracycline adsorption performance test will be carried out on the CDI device. The experimental device consists of a 10 cm × 10 cm glass plate, a 2 cm thick silica gel sheet, a bamboo-based porous carbon electrode sheet and a graphite plate. A 1.2 V CDI is driven by a DC power supply and a peristaltic pump is used at a speed of 20 mL min. -1 The treated solution was injected into the CDI device at a constant flow rate of 1.5 %. All experiments were carried out in a total volume of 100 mL of solution, the temperature was controlled at 298 K, and the absorbance of the solution after the test was measured at a wavelength of 358 nm.
[0072] The test found that the infrared spectra of the product obtained in this example before and after TC adsorption were similar to those in Example 1, both at 1110 cm -1 、1597 cm -1 and 2350 cm -1 There are obvious characteristic peaks on the left and right, indicating that the bamboo cellulose-based porous carbon has obvious adsorption of tetracycline, and also shows good cycle stability in the regeneration cycle experiment. Example 5
[0073] 1. Extraction of bamboo cellulose 5g of washed and dried bamboo blocks were placed in a sealed container, and 35mL of tetramethylguanidine, 20mL of N,N-dimethylformamide and 20mL of water were added respectively. The mixture was reacted at a high temperature of 170℃ for 5h to obtain a mixture. The reaction mixture was stirred, filtered and washed. The filtered solid was placed in 50mL of an aqueous solution containing 0.5% hydrogen peroxide, 0.3% sodium hydroxide, 0.05% magnesium sulfate and 0.3% sodium silicate, bleached at 70℃ for 3h, and then separated to obtain bamboo cellulose with a yield of 47.2% and an extracted solid cellulose content of 97.3%.
[0074] 2. Preparation of electrode adsorption materials (i) Add 2.36 g of the extracted bamboo cellulose into 188.8 g of 7% LiCl / DMAc solution and stir at 80°C for 6 h until the bamboo cellulose is fully dissolved to obtain a bamboo cellulose solution.
[0075] (ii) Take 80 g of bamboo cellulose solution, add 2 g of ethylene glycol and dilute to a solid content of 1.2%, then add pre-dried sodium chloride (0.492 g). At this time, the mass ratio of bamboo cellulose to sodium chloride is about 1:0.5. After preliminary stirring, ultrasonic dispersion is performed to obtain a dispersion system.
[0076] (III) The dispersion system is atomized and introduced into a high-temperature tube furnace filled with nitrogen, and one-step solidification and pyrolysis are performed at 700°C. After natural cooling, the pyrolysis products are collected by washing with ethanol to obtain a mixed solution. Deionized water and dilute hydrochloric acid are added to the mixed solution, and ultrasonic dispersion and washing and centrifugation are performed. The supernatant is poured off, and the solid product is collected and dried for 2 days to obtain bamboo charcoal microspheres with a porous structure.
[0077] 3. Product morphology analysis and performance testing The morphology of the product obtained in this example is similar to that in Example 1. The particle size of the product is about 1-2 μm, and it is in the form of porous microspheres. The product also has a loose organizational structure, a large number of microchannels are formed in the microspheres, and the surface is rich in nitrogen and oxygen elements.
[0078] The bamboo-based porous carbon electrode sheet is composed of 80% active material (about 0.2 g of bamboo-based porous carbon), 10% conductive agent (about 0.025 g of Super P) and 10% binder (about 0.025 g of PTFE). First, the three materials are uniformly mixed into a slurry in an ethanol solution, and then rolled into a sheet with a thickness of 0.1 mm, an area of 4.0 cm × 4.0 cm and a weight of 40 mg, which is then pressed on graphite paper and placed in a 120°C oven for drying for 24 h to obtain a bamboo-based porous carbon electrode sheet for CDI devices.
[0079] When conducting the tetracycline adsorption experiment on bamboo-based porous carbon, the tetracycline adsorption performance test will be carried out on the CDI device. The experimental device consists of a 10 cm × 10 cm glass plate, a 2 cm thick silica gel sheet, a bamboo-based porous carbon electrode sheet and a graphite plate. A 1.2 V CDI is driven by a DC power supply and a peristaltic pump is used at a speed of 20 mL min. -1 The treated solution was injected into the CDI device at a constant flow rate of 1.5 %. All experiments were carried out in a total volume of 100 mL of solution, the temperature was controlled at 298 K, and the absorbance of the solution after the test was measured at a wavelength of 358 nm.
[0080] The test found that the infrared spectra of the product obtained in this example before and after TC adsorption were similar to those in Example 1, both at 1110 cm -1 、1597 cm -1 and 2350 cm -1 There are obvious characteristic peaks on the left and right, indicating that the bamboo cellulose-based porous carbon has obvious adsorption of tetracycline, and also shows good cycle stability in the regeneration cycle experiment. Example 6
[0081] 1. Extraction of bamboo cellulose 3g of washed and dried bamboo blocks were placed in a sealed container, and 10g of pyrrolidone, 10mL of tetrahydrofuran and 30mL of water were added respectively. The mixture was reacted at a high temperature of 160℃ for 2h to obtain a mixture. The reaction mixture was stirred, filtered and washed. The filtered solid was placed in an aqueous solution containing 30mL of 0.5% hydrogen peroxide, 0.5% sodium hydroxide, 0.02% magnesium sulfate and 0.2% sodium silicate, bleached at 50℃ for 7h, and then separated to obtain bamboo cellulose, with a yield of 46.1% and an extracted solid cellulose content of 95.1%.
[0082] 2. Preparation of electrode adsorption materials (i) Add 1.383 g of the extracted bamboo cellulose into 82.98 g of 9% LiCl / DMAc solution and stir at 60°C for 5 h until the bamboo cellulose is fully dissolved to obtain a bamboo cellulose solution.
[0083] (ii) Take 60 g of bamboo cellulose solution, add 10.29 g of ethylene glycol and dilute to a solid content of 1.4%. Then, add pre-dried nano-calcium carbonate (1.476 g) under stirring. At this time, the mass ratio of bamboo cellulose to nano-calcium carbonate is about 1:1.5. After preliminary stirring, ultrasonic dispersion is performed to obtain a dispersion system.
[0084] (III) The dispersion system is atomized and introduced into a high-temperature tube furnace filled with nitrogen, and one-step solidification and pyrolysis are performed at 700°C. After natural cooling, the pyrolysis products are collected by washing with ethanol to obtain a mixed solution. Deionized water and dilute hydrochloric acid are added to the mixed solution, and ultrasonic dispersion and washing and centrifugation are performed. The supernatant is poured off, and the solid product is collected and dried for 1 day to obtain bamboo charcoal microspheres with a porous structure.
[0085] 3. Product morphology analysis and performance testing.
[0086] The morphology of the product obtained in this example is similar to that in Example 1. The particle size of the product is about 1.5-2 μm, and it is in the form of porous microspheres. The product also has a loose organizational structure, a large number of microchannels are formed in the microspheres, and the surface is rich in nitrogen and oxygen elements.
[0087] The bamboo-based porous carbon electrode sheet is composed of 80% active material (about 0.2 g of bamboo-based porous carbon), 10% conductive agent (about 0.025 g of Super P) and 10% binder (about 0.025 g of PTFE). First, the three materials are uniformly mixed into a slurry in an ethanol solution, and then rolled into a sheet with a thickness of 0.1 mm, an area of 4.0 cm × 4.0 cm and a weight of 40 mg, which is then pressed on graphite paper and placed in a 120°C oven for drying for 24 h to obtain a bamboo-based porous carbon electrode sheet for CDI devices.
[0088] When conducting the tetracycline adsorption experiment on bamboo-based porous carbon, the tetracycline adsorption performance test will be carried out on the CDI device. The experimental device consists of a 10 cm × 10 cm glass plate, a 2 cm thick silica gel sheet, a bamboo-based porous carbon electrode sheet and a graphite plate. A 1.2 V CDI is driven by a DC power supply and a peristaltic pump is used at a speed of 20 mL min. -1 The treated solution was injected into the CDI device at a constant flow rate of 1.5 %. All experiments were carried out in a total volume of 100 mL of solution, the temperature was controlled at 298 K, and the absorbance of the solution after the test was measured at a wavelength of 358 nm.
[0089] The test found that the infrared spectra of the product obtained in this example before and after TC adsorption were similar to those in Example 1, both at 1110 cm -1 、1597 cm -1 and 2350 cm -1 There are obvious characteristic peaks on the left and right, indicating that the bamboo cellulose-based porous carbon has obvious adsorption of tetracycline, and also shows good cycle stability in the regeneration cycle experiment.
[0090] In summary, the reaction reagents involved in the process of preparing the target product in the above embodiments are few, and the bamboo-based porous carbon microspheres with porous microsphere morphology are finally prepared by one-step curing and pyrolysis in each embodiment. The process can be expanded in large quantities and meets the requirements of industrial production for high efficiency and low cost. Since the synthesized bamboo-based porous carbon microspheres have the characteristics of being porous, large specific surface area, and dual doping with nitrogen / oxygen elements, and the material has good electrical conductivity and hydrophilicity, and has abundant adsorption sites and ion transmission channels, the material has a high adsorption capacity and shows good cycle stability in the regeneration cycle experiment.
[0091] The above embodiments are preferred implementation schemes of the present invention. In addition, the present invention may also be implemented in other ways. Any obvious replacement without departing from the concept of the present technical solution is within the protection scope of the present invention.
[0092] Finally, it should be emphasized that in order to allow ordinary technicians in the field to more easily understand the improvements of the present invention over the prior art, some descriptions of the present invention have been simplified, and for the sake of clarity, some other elements are omitted in this application document. Those skilled in the art should realize that these omitted elements may also constitute the content of the present invention.
Claims
1. A method for preparing bamboo-based porous carbon microspheres, characterized in that: The following steps are involved: S1. Put the bamboo block into a sealed container, add organic base A and solvent B, react at 130-170°C to obtain a mixture, pulp it, separate it to obtain crude fiber, then put the crude fiber into solvent C, bleach it at 50-70°C, and then separate it to obtain bamboo cellulose; S2. adding bamboo cellulose to solvent D and stirring at 50-80° C. to obtain a bamboo cellulose solution; S3. The bamboo cellulose solution is diluted with an organic solvent, inorganic particles are added, and a dispersion is obtained after ultrasonic dispersion; S4. The dispersion is atomized and passed into a heating container, cured and pyrolyzed at 400-1200° C., and a mixed solution is obtained after cooling. The mixed solution is then ultrasonically dispersed and centrifuged to obtain a solid product, namely, bamboo-based porous carbon microspheres.
2. The method for preparing bamboo-based porous carbon microspheres according to claim 1, characterized in that: In step S1, the molar ratio of the organic base A to the solvent B is 1:(4-16).
3. The method for preparing bamboo-based porous carbon microspheres according to claim 1, characterized in that: In step S1, the organic base A is selected from at least one of dibutylamine, tetramethylguanidine, N-methylformamide, and pyrrolidone, the solvent B is selected from at least one of tetrahydrofuran, N,N-dimethylformamide and water, and the solvent C is an aqueous solution containing 0.3-1% hydrogen peroxide, 0.2-0.5% sodium hydroxide, 0.02-0.05% magnesium sulfate, and 0.05-0.3% sodium silicate.
4. The method for preparing bamboo-based porous carbon microspheres according to claim 1, characterized in that: In step S2, the solvent D is a LiCl / DMAc solution with a concentration of 6%-10%.
5. The method for preparing bamboo-based porous carbon microspheres according to claim 1, characterized in that: In step S2, the mass ratio of the bamboo cellulose to the solvent D is 1:(60-80).
6. The method for preparing bamboo-based porous carbon microspheres according to claim 1, characterized in that: In step S3, the organic solvent is ethylene glycol or N,N-dimethylformamide, and the inorganic particles are selected from at least one of nano calcium carbonate, lithium chloride, potassium chloride, and sodium chloride.
7. The method for preparing bamboo-based porous carbon microspheres according to claim 1, characterized in that: In step S3, the mass ratio of bamboo cellulose to inorganic particles in the dispersion is 1:(0.5-2).
8. A bamboo-based porous carbon microsphere, characterized in that: The porous carbon microspheres are prepared by the method for preparing the bamboo-based porous carbon microspheres according to any one of claims 1 to 7.
9. A capacitor deionization electrode material, characterized in that: The invention comprises the bamboo-based porous carbon microspheres as claimed in claim 8.
10. The use of the capacitor deionization electrode material according to claim 9, characterized in that: Used to remove tetracycline antibiotics from water.
Citation Information
Patent Citations
Small organic molecule cracked carbon, preparation method thereof, capacitive deionization unit and capacitive deionization system
CN112010404A